Short Communication: Augmentation of cardioprotective effect of captopril by Costus speciosus against isoproterenol induced myocardial toxicity in rats - ABDULRAHMAN A.I. AL-YAHYA; MOHAMMED ASAD; ABDULMONIEM SADABY; KHALID ELFAKKI IBRAHIM (Nusantara Bioscience, 2017)
Al-Yahya AAI, Asad M, Sadaby A, Ibrahim KE. 2017. Short Communication: Augmentation of cardioprotective effect of captopril by Costus speciosus against isoproterenol induced myocardial toxicity in rats. Nusantara Bioscience 9: 295-299. This study determined the pharmacodynamic interaction of captopril, a known cardioprotective effect with methanolic extract of Costus speciosus rhizomes (Costaceae) that is known for its powerful antioxidant action during isoproterenol induced cardiac toxicity in rats. A methanolic extract of the rhizomes was prepared by maceration. Rats were administered the methanolic extract at two different doses of 200 mg/k or 400 mg/kg orally and captopril was administered orally at a dose of 30 mg/kg. All the drugs alone or in combination were once daily for two weeks. At the end of treatment period, two doses of isoproterenol (150 mg/kg, s.c) were administered to rats at 24 hr interval. Blood was withdrawn to estimate creatinine kinase-MB (CK-MB) activities. The heart tissue was subjected to histological examinations to determine the extent of damage. Isoproterenol induced severe damage to the myocardium that was indicated through an elevation in serum CK-MB activity and the same was confirmed by histological examinations. Costus speciosus at both the tested doses attenuated the damage produced by isoproterenol. Both the doses caused a decrease in the biomarker activity as well as reduced the myocardial damage as observed in histological examination. A similar effect was observed with captopril. The co-administration of captopril with either dose of Costus speciosus demonstrated excellent cardioprotection suggesting that combination of this herb with captopril augments its cardioprotective action. It was concluded that Costus speciosus shows dose-dependent cardioprotection and augments the cardioprotective effect of captopril during isoproterenol induced cardiotoxicity in rats.